Authentication and accounting for network services in next-generation mobile networks - Tewari, Hitesh (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2005)
Mobile communications technologies are in a constant state of flux. They have evolved from simple one-way radio communications systems, to today’s third-generation networks that support digital signaling and multimedia messaging. Traditionally mobile networks have been built and operated by large telecommunications network operators on a region or country wide basis. Such operators usually have roaming agreements to allow mobile users who roam outside of their home network to seamlessly access network services in foreign networks, and rely on trust-based billing techniques to charge for network usage in order to maintain their revenue streams. It is envisaged that the next generation of mobile networks will consist of large numbers of wireless access networks comprising heterogeneous radio access technologies. These networks will be centered on a highspeed network core with IP as the main transmission and communications protocol. With large numbers of different sized independent network operators, value-added service providers and millions of roaming mobile users, there is a need to remove the implicit trust relationships between them, in order to provide simplified authentication procedures and incontestable charging for network services. Also the emergence of mobile ad hoc networks has sparked a great deal of interest in the employing them as a flexible tool in extending the reach of the fixed networking infrastructure in next-generation networks. However ad hoc networks usually consist of closed user groups and require all the nodes in the network to cooperate in the routing of packets. The limited battery life of mobile nodes is an important factor, and users must be compensated for forwarding packets on behalf of other nodes in the network. In addition, the presence of malicious nodes can disrupt of the cooperative nature of the network and lead to transmission failures. The issues of authentication and accounting in next-generation mobile networks are addressed by designing a micropayment scheme that allows the access network operator to be paid in real time for service provision, and provides for the simultaneous authentication of routing update messages in the network. Next the issue of compensating nodes in an ad hoc network for packet forwarding is addressed by extending the basic payment scheme to provide a flexible multi-party micropayment system for ad hoc networks. Also the problem of misbehaving nodes in ad hoc networks is explored. A secure routing and packet forwarding scheme has been developed to counteract the presence of malicious nodes in ad hoc networks which may advertise false routes or intermittently drop packets that are not destined for them to disrupt the flow of datagrams in the network. Further, a prototype of each of the above three protocols has been implemented on a well known network simulator. Finally, experimental measurements of cryptographic algorithms that were employed as part of this thesis have been benchmarked on a PDA in order to evaluate their suitability on such constraint devices.
Keywords: Computer Science, Ph.D.; Ph.D. Trinity College Dublin